2012
DOI: 10.1016/j.appet.2012.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Associations of food preferences and household food availability with dietary intake and quality in youth with type 1 diabetes

Abstract: The objective of this study was to examine associations of food preferences and availability with dietary intake in youth with type 1 diabetes, for whom dietary intake and quality are essential to disease management. Youth (n=252, age 13.2±2.8y, diabetes duration 6.3±3.4y) reported preferences and parents reported household availability for 61 food items categorized as fruit, vegetables, whole grains, refined grains and fats/sweets. Youth energy-adjusted daily servings of food groups, Healthy Eating Index-2005… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 42 publications
(55 reference statements)
1
19
0
Order By: Relevance
“…Sample sizes ranged from ninety subjects (26) to 13 305 (15) . Studies were conducted with children of various age groups, with one study targeting pre-schoolers (24) , six targeting children (15)(16)(17)22,23,25) and eight targeting adolescents (19)(20)(21)(26)(27)(28)(29)(30) .…”
Section: Overview Of Study Characteristics For Included Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…Sample sizes ranged from ninety subjects (26) to 13 305 (15) . Studies were conducted with children of various age groups, with one study targeting pre-schoolers (24) , six targeting children (15)(16)(17)22,23,25) and eight targeting adolescents (19)(20)(21)(26)(27)(28)(29)(30) .…”
Section: Overview Of Study Characteristics For Included Studiesmentioning
confidence: 99%
“…With the exception of a study by Lipsky et al (29) , which was conducted with type 1 diabetics, all studies were conducted with healthy participants. Seven studies reported the ethnicity of their subjects, with non-Whites ranging from 24 % to 100 % of the sample (19,(24)(25)(26)(27)(28)30) .…”
Section: Overview Of Study Characteristics For Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations